Low‐Temperature Growth of Carbon Nanotubes Catalyzed by Sodium‐Based Ingredients. (27th May 2019) - Li, Richard; Antunes, Erica F.; Kalfon‐Cohen, Estelle; Kudo, Akira; Acauan, Luiz; Yang, Wei‐Chang D.; Wang, Canhui; Cui, Kehang; Liotta, Andrew H.; Rajan, Ananth Govind; Gardener, Jules; Bell, David C.; et al.
Abstract: Synthesis of low‐dimensional carbon nanomaterials such as carbon nanotubes (CNTs) is a key driver for achieving advances in energy storage, computing, and multifunctional composites, among other applications. Here, we report high‐yield thermal chemical vapor deposition (CVD) synthesis of CNTs catalyzed by reagent‐grade common sodium‐containing compounds, including NaCl, NaHCO3, Na2 CO3, and NaOH, found in table salt, baking soda, and detergents, respectively. Coupled with an oxidative dehydrogenation reaction to crack acetylene at reduced temperatures, Na‐based nanoparticles have been observed to catalyze CNT growth at temperatures below 400 °C. Ex situ and in situ transmission electron microscopy (TEM) reveal unique CNT morphologies and growth characteristics, including a vaporizing Na catalyst phenomenon that we leverage to create CNTs without residual catalyst particles for applications that require metal‐free CNTs. Na is shown to synthesize CNTs on numerous substrates, and as the first alkali group metal catalyst demonstrated for CNT growth, holds great promise for expanding the understanding of nanocarbon synthesis. Abstract : Kohlenstoff‐Nanoröhren (CNTs) lassen sich mit handelsüblichen Inhaltsstoffen, die Na enthalten, synthetisieren. Speisesalz, Natron, Lauge und Waschsoda werden auf Substraten abgelagert und einem Niedertemperatur‐Prozess der chemischen Dampfabscheidung (CVD) unterhalb 400 °C unterzogen, wodurch CNTs entstehen. Übriger Na‐Katalysator wird durch inertes Glühen entfernt, was zu katalysatorfreien CNTs führt.